Ferns and Lycophytes of Honduras: A new annotated checklist - Reyes-Chávez, Johan; Tarvin, Stephanie; Batke, Sven Peter (Phytotaxa, 2021)
For over two decades no attempt has been made to update the checklist of Ferns and Lycophytes (hereafter only referred to as pteridophytes) of Honduras. In 1996 Nelson-Sutherland and co-workers published the first fully annotated checklist for the country, which included 651 named species (680 taxa including varieties and hybrids). However, phylogenetic relationships have changed substantially since then. There have also been many taxonomic revisions for several groups and a considerable number of new records have since been published. Our work aimed to provide a comprehensive updated and fully annotated checklist of Honduran ferns. We undertook a comprehensive literature review of new records for Honduras and verified each individual record for the country. We followed PPGI for our taxonomic species revisions. We excluded a total of 81 taxa from the original 1996 checklist due to synonymy or lack of evidence of the species occurrence in Honduras. A total of 114 new species records were added, including four previously unpublished records. Our new updated checklist includes 713 taxa (including 8 varieties and 7 hybrids) which represents a 19% increase to the number of pteridophytes known from Honduras. Our work provides updated information regarding the pteridophytes diversity of Honduras. These data provide a crucial first step towards the first Honduran pteridophytes flora.